Financial Health of Leading SOEs: Altman Z-Score Analysis on LQ45 Issuers - Rasid, Ayub Usman; Olilingo, Fahrudin Zain; Hasanuddin, Hasanuddin; Gani, Roydah (AIBPM Publisher, 2025)
This study aims to evaluate the financial health of selected state-owned enterprises (SOEs) listed in the LQ45 index during the 2019–2023 period using the Altman Z-Score method. This approach combines five key financial ratios to assess the bankruptcy potential of firms. Secondary data were collected from annual financial reports and analyzed longitudinally and cross-sectorally. The results reveal that only PT Bukit Asam (PTBA) and PT Telkom Indonesia (TLKM) consistently remained in the safe zone (Z 2.99), while most other companies, particularly in the banking and infrastructure sectors, were classified in the grey or distress zones, indicating a significant bankruptcy risk. These findings highlight the financial resilience disparities across sectors within SOEs, despite structural support from the government. The study concludes that the Altman Z-Score model serves as an effective early warning tool for assessing financial risk, although sector-specific interpretation, especially for the financial services industry, is necessary. The implications suggest that corporate management should enhance operational efficiency, strengthen capital structure, and establish early warning systems based on financial ratios to improve long-term financial resilience.